(untitled) (Biological Sciences - PJSIR, 2022)
Using Wilson’s FG matrix method, a normal coordinate analysis of the spectral frequencies and form of the zerowave vector vibrations of the high temperature superconductor Er Ba2Cu)07 have been performed, The vibrational frequencies and potential energy distribution of 21 infrared active and IS Raman active modes are presented. The potential constants employed here are given and the evaluated vibrational frequencies are compared with the available experimental values.